Novel Antimicrobial Cellulose Fleece Inhibits Growth of Human-Derived Biofilm-Forming Staphylococci During the SIRIUS19 Simulated Space Mission - Wischer, Daniela; Schneider, Dominik; Poehlein, Anja; Herrmann, Friederike; Oruc, Harun; Meinhardt, Junias; Wagner, Olaf; Ahmed, Rameez; Kharin, Sergey; Novikova, Natalia; Haag, Rainer; Daniel, Rolf; et al. (Frontiers in Microbiology, 2020)
Two novel antimicrobial surface coatings were assessed for their lasting antibacterial effect under simulated space conditions during the SIRIUS-19 study. Because long-term space travel can affect the human immune system, astronauts are particularly susceptible to infectious disease. Moreover, the space flight environment can alter the composition of microbial communities within the spacecraft and increase bacterial virulence and resistance to antibiotics. In addition to protecting the crew from infection by human pathogens, prevention and elimination of bacterial contamination is important to avoid corrosion and damage of the technical equipment. The antimicrobial coating AGXX® consists of micro-galvanic cells composed of silver and ruthenium which damage bacterial cells through the release of reactive oxygen species. Over the last years, several studies on the antimicrobial effect of AGXX® have demonstrated an effective inhibition of growth and even complete elimination of many pathogenic bacteria - including multiresistant microorganisms - as well as their biofilms. The second antimicrobial coating, GOX, consists of chemically modified graphene oxide. Through a positive surface charge and its flexible scaffold, GOX can multivalently bind and immobilize bacteria via electrostatic attraction. Here, AGXX® and GOX were applied to non-metallic carriers not previously tested. The antimicrobial coated materials, as well as uncoated control samples, were exposed in the SIRIUS artificial space module and analyzed at different time points during the 4-months isolation study. Survival and growth of airborne heterotrophic, aerobic bacteria on the surfaces were assessed by cultivation-based methods, employing growth conditions suitable for potential human pathogens. Human-associated, biofilm-forming Staphylococcus spp. (S. hominis, S. haemolyticus, S. epidermidis) strongly dominated at all time points, most were resistant against erythromycin, kanamycin and ampicillin. AGXX® coatings completely inhibited growth of these opportunistic pathogens on all tested surface materials. Particularly, AGXX®-cellulose fleece achieved a clear reduction in bacterial load able to recover post contact. GOX-cellulose fleece effectively immobilized bacteria. Sequence analysis of 16S rRNA gene amplicons revealed that the isolated Staphylococcus spp. did not dominate the overall bacterial community, accounting for only 0.1-0.4% of all sequences. Instead, molecular data revealed Lactobacillus, Comamonas, Pseudomonas, Sporosarcina and Bacillus as the dominant genera across all samples and time points.